2012
DOI: 10.1016/j.gca.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The silicon isotope composition of granites

Abstract: Because weathering results in preferential incorporation of the lighter Si isotopes into clay minerals, the Si in magmas derived from (meta)sedimentary lithologies enriched in such phases should also be isotopically light, relative to melts derived from igneous sources. With the advent of new high precision techniques it should therefore be possible to resolve such differences. Hence, Si isotopes have to potential to distinguish between, and characterise, different magmatic source regions.To explore this, here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 81 publications
(132 reference statements)
6
55
1
Order By: Relevance
“…In assessing δ 30 Si variations in granites, Savage et al (2012Savage et al ( , 2014 found A-and I-type granites generally conform to the igneous magmatic differentiation trend but that S-type granites deviated to significantly lower δ 30 Si. The light isotopic signatures of the latter are attributed to the partial melting of isotopically light metasedimentary components (Savage et al, 2012(Savage et al, , 2014 during the S-type granite genesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In assessing δ 30 Si variations in granites, Savage et al (2012Savage et al ( , 2014 found A-and I-type granites generally conform to the igneous magmatic differentiation trend but that S-type granites deviated to significantly lower δ 30 Si. The light isotopic signatures of the latter are attributed to the partial melting of isotopically light metasedimentary components (Savage et al, 2012(Savage et al, , 2014 during the S-type granite genesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to recent advances in mass spectrometry, several stable isotopic systems including Fe (e.g., Poitrasson and Freydier, 2005;Heimann et al, 2008;Schuessler et al, 2009) and Si (e.g., Douthitt, 1982;Ding et al, 1996;Savage et al, 2011Savage et al, , 2012Zambardi and Poitrasson, 2011) now show analytically significant and systematic variations during magmatic differentiation. While these data provide new insight into magmatic differentiation, explanations of how the fractionations occur remain debated, in part due to different isotopic systems being used in separate studies.…”
Section: Introductionmentioning
confidence: 99%
“…The two Archaean-age Pilbara shales from Australia are 259 both isotopically much lighter than igneous rocks (sample Pg-7 displays the lightest δ 30 Si value 260 analysed in this study, viz. The data described above show that, with respect to Si isotopes, the UCC is heterogeneous 277 relative to the mantle and igneous rocks (Savage et al, 2010(Savage et al, , 2011(Savage et al, , 2012. The following discussion 278 concerns how these data can be used to constrain the Si isotopic composition of the modern day UCC, 279 as well as interpreting the Si isotope composition of clastic sedimentary material in terms of what is 280 already known about possible sources and Si isotope fractionation as a result of low temperature, 281 critical zone, processes.…”
Section: External Standards 219mentioning
confidence: 99%
“…While pristine (unweathered) silicate rocks usually display uniform Si isotopic compositions on continents (d 30 Si $ À0.3 ± 0.2‰; e.g. Savage et al, 2010Savage et al, , 2012), their alteration leads to weathering products having very distinctive Si isotopic ratios: a dissolved pool characterized by positive d 30 Si values (up to $+4.7‰; e.g. De la https://doi.org/10.1016/j.gca.2018.03.015 0016-7037/Ó 2018 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%